Clinical Rotation Handbook Promotes Orthopaedic Resident Wellness: A Quality Improvement Study - Rogers, Joshua; Kim, Faith; Strine, Brayden; Lancaster, Benjamin; Hofer, Kevin; Blankespoor, Michael; Nentwig, Michelle; Dart, Bradley; Hearon, Bernard (Kansas Journal of Medicine, 2022)
Introduction. Transitioning from one clinical rotation to the next may be particularly stressful for orthopaedic residents attempting to navigate new work environments with new faculty mentors and new patients. The purpose of this quality improvement (QI) project was to determine if resident stress could be improved by using a handbook to disseminate key rotation-specific data during quarterly rotation transition periods. Methods. A comprehensive electronic handbook was created by residents to describe each rotation in our orthopaedic training program in terms of: (1) faculty and staff contact data, (2) daily clinic and surgery schedules, (3) resident responsibilities and faculty expectations, and (4) key resources and documents. At rotation transition, a session in the academic schedule was dedicated for outgoing residents to update the handbook and to sign-out to incoming residents. Pre- and post-handbook questionnaires were administered to assess resident perceptions of stress or anxiety, preparedness, and confidence before commencing the new rotation. Nonparametric data derived from the surveys were analyzed using the sign test choosing p < 0.05 for a two-tailed test as the level of statistical significance. Results. Most residents perceived improvements in stress/anxiety, preparedness, and confidence understanding rotation expectations after the handbook was implemented. Changes in these three outcome parameters were statistically significant. Conclusions. This rotation transition QI initiative consisting of a resident-authored, rotation-specific electronic handbook and dedicated verbal sign-out session enhanced resident wellness by decreasing stress, increasing preparedness, and improving confidence among residents starting a new rotation. Similar online resources may be useful for trainees in other specialties.